Caracterización de las buenas prácticas ambientales aplicadas por las empresas del sector curtidor del Quindío y su relación con el indicador de valor económico agregado EVA. (2011)
The present investigation had as purpose to verify the possibility that the good ones practical environmental (pre-process, process and post-process) applied they generate value in the companies of the sector tanner of the Quindío, especially in the tanneries of the Sidewalk The María, by means of the persistent and intentional observation and with the use of surveys and interviews.